When sport event work stopped: Exposure of sport event labor precarity by the COVID-19 pandemic - Sheptak Jr., R. D.; Menaker, B. E. (International Journal of Sport Communication, 2020)
The COVID-19 pandemic of 2020 has led to a collapse in the economic, governmental, and social structures that have defined globalized society in the 21st century. The hit to the labor market may be the most striking. In the first 6 weeks of the pandemic-forced restrictions, more than 30 million Americans filed for unemployment benefits (Swartz, Hsu, & Cohen, 2020), many of those in service industry jobs. In addition, the U.S. economy contracted 4.8% in the first quarter of 2020, the worst contraction of the economy since the 2008 Great Recession (Casselman, 2020). The sports industry in the United States has not been immune to the impact of the pandemic. Like many service sector businesses, the industry has effectively shut down, and work associated with sport has ceased while the games are on hold. Historically, issues with laborers who support sporting events have been largely ignored in the media and sport management literature. However, recent decisions driven in response to the COVID-19 outbreak to suspend play in major leagues has thrust the plight of sport event and venue workers, albeit briefly, to the forefront of media coverage. Prime-time news segments exposed the precarious nature of the work situation that hourly event and venue workers found themselves in. Essentially, when the games stopped, so did the work.